The Relationship of Legal Subjects in Making Agreements Without Conducting Face-to-Face Meetings Based on the Artificial Intelligence (AI) Ecosystem: Business Law Implementation - Ahmad Suryadi S; Suprianto Suprianto; Munadi Agri Saswan; Siti Rahmi (Asha Publishing, 2025)
The development of Artificial Intelligence (AI)-based technology has presented new challenges in treaty law, especially regarding the validity of legal relations that occur without face-to-face meetings. This study uses a normative-empirical method to analyze the application of treaty law in the context of the AI ecosystem. The purpose of this study is to understand the relationship between the legal terms of agreements based on Article 1320 of the Civil Code and the practice of agreements made through AI-based digital media. The data sources came from a literature study of laws and regulations, jurisprudence, and online treaty practices. Data collection techniques are carried out through literature studies and participatory observation of the implementation of AI in community legal interactions. The data analysis technique uses the law enforcement approach and the concept of recht vacuum to assess whether there is a legal vacuum. The results of the study show that agreements made through AI are still declared valid and binding as long as they meet the legal elements of the agreement according to the Civil Code, except for certain types of agreements that legally require face-to-face meetings such as land buying and selling, notary deeds, and grants, in accordance with the provisions of Law Number 1 of 2024 concerning Information and Electronic Transactions